The role of neutrophils in osteosarcoma: insights from laboratory to clinic - Xia, Ming; Han, Yu; Sun, Lihui; Li, Dongbo; Zhu, Chunquan; Li, Dongsong (Frontiers in Immunology, 2024)
Osteosarcoma, a highly aggressive malignant bone tumor, is significantly influenced by the intricate interactions within its tumor microenvironment (TME), particularly involving neutrophils. This review delineates the multifaceted roles of neutrophils, including tumor-associated neutrophils (TANs) and neutrophil extracellular traps (NETs), in osteosarcoma’s pathogenesis. TANs exhibit both pro- and anti-tumor phenotypes, modulating tumor growth and immune evasion, while NETs facilitate tumor cell adhesion, migration, and immunosuppression. Clinically, neutrophil-related markers such as the neutrophil-to-lymphocyte ratio (NLR) predict patient outcomes, highlighting the potential for neutrophil-targeted therapies. Unraveling these complex interactions is crucial for developing novel treatment strategies that harness the TME to improve osteosarcoma management.